The dialectic of position and maneuver : understanding Gramsci's military metaphor - Egan, Daniel, 1963- (Studies in critical social sciences, 2016)
"In The Dialectic of Position and Maneuver, Daniel Egan examines the role that the military metaphors of war of position and war of maneuver play in Antonio Gramsci's social theory. The foundation for this analysis is the different ways in which Marxists have understood war and military strategy since the mid-nineteenth century. In doing so, Egan argues that the distinction between war of position and war of maneuver which is so central to Gramsci's work as well as contemporary interpretations of his work must be understood in a more dialectical manner. This conclusion is important not only in terms of Gramsci's social theory, but also for understanding the limits and possibilities of contemporary political strategies for the left worldwide."--Provided by publisher